OTALIK MEHRINING NARXI: VIJDON SAHIFALARIDA BITILGAN IMTIHON (Said Ahmadning “Ufq” romanidagi Ikromjon va Tursunboy obrazlari talqinida) - Ubaydullayeva Gulbahor Fozil qizi; X.Q.Hamroqulova (Ustozlar uchun, 2025)
This article is devoted to exploring the father-child relationship, the responsibilities of fatherhood, and the spiritual and psychological consequences of neglecting these duties, based on the characters Ikromjon and Tursunboy from Said Ahmad’s novel "Ufq" ("The Horizon"). The novel artistically analyzes how the dreams born in the heart of a devoted, honest, patient, and honorable father are shattered—how these dreams, unable to cross the threshold into reality, turn into inner torment. Through the character of Ikromjon, the traditional family values of the Uzbek people, their moral standards, and the paternal upbringing built on patience and compassion are vividly portrayed. In contrast, Tursunboy represents a child who denies that compassion, fails to appreciate his father’s selflessness, and is ultimately condemned to live in spiritual anguish caused by his own mistakes. The article highlights the role of the father figure in the system of societal values, interpreting concepts such as conscience, dignity, duty, and honesty through a literary lens, closely linking them to contemporary issues of family and upbringing. The analysis primarily focuses on character psychology, internal conflicts, and ideological clashes. This research serves to reflect on the current state of national spirituality, values, and education through artistic characters in Uzbek prose.